2022
DOI: 10.1002/cne.25355
|View full text |Cite
|
Sign up to set email alerts
|

Structural arrangement of auditory brainstem nuclei in the bats Phyllostomus discolor and Carollia perspicillata

Abstract: The structure of the mammalian auditory brainstem is evolutionarily highly plastic, and distinct nuclei arrange in a species-dependent manner. Such anatomical variability is present in the superior olivary complex (SOC) and the nuclei of the lateral lemniscus (LL). Due to the structure-function relationship in the auditory brainstem, the identification of individual nuclei supports the understanding of sound processing. Here, we comparatively describe the nucleus arrangement and the expression of functional ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(22 citation statements)
references
References 126 publications
5
17
0
Order By: Relevance
“…Calbindin immunoreactivity in neurons appears in the DLL and in a few VLL neurons of adult rats (Friauf, 1994), a pattern distinct to that observed in the mouse where Calb1 is expressed in the VLL and a few ILL neurons (present work). This latter pattern is on the whole similar to that described in two distant species, the mustached bat (Zettel et al, 1991) and the chinchilla (Kelley et al, 1992), although interspecies differences between bats have been reported (Pätz et al, 2022). These results suggest significant evolutionary differences in the expression of this molecule as previously proposed (Joven et al, 2013), in addition to the variations in Calbindin expression in the brain at different developmental stages including the auditory nuclei (Förster and Illing, 2000).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Calbindin immunoreactivity in neurons appears in the DLL and in a few VLL neurons of adult rats (Friauf, 1994), a pattern distinct to that observed in the mouse where Calb1 is expressed in the VLL and a few ILL neurons (present work). This latter pattern is on the whole similar to that described in two distant species, the mustached bat (Zettel et al, 1991) and the chinchilla (Kelley et al, 1992), although interspecies differences between bats have been reported (Pätz et al, 2022). These results suggest significant evolutionary differences in the expression of this molecule as previously proposed (Joven et al, 2013), in addition to the variations in Calbindin expression in the brain at different developmental stages including the auditory nuclei (Förster and Illing, 2000).…”
Section: Discussionsupporting
confidence: 88%
“…However, the ISH experiments analyzed in the present work seem to lack sensitivity to discern this gradient, which was witnessed through fluorescent immunohistochemistry. Alternatively, Hcn1 and the Kcna1 channel are expressed across the entire LLN in bats, a pattern that may be functionally related to the echolocation characteristic of these species ( Pätz et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kcna1 |Kv1.1 was DEG#92 in pLSOs ( Figure 9A ). Kv α subunits have received extensive attention in the auditory brainstem, and immunoreactivity has been demonstrated in several species in somata, dendrites, and axon terminals (mouse: Wang et al, 1994 ; Brew et al, 2003 ; rat: Barnes-Davies et al, 2004 ; gerbil: Nabel et al, 2019 ); three bat species: ( Rosenberger et al, 2003 ; Pätz et al, 2022 ). Kv1.1 channels were most intensively analyzed.…”
Section: Discussionmentioning
confidence: 99%
“…No band was seen in VGluT1 knockout mice (manufacturer's datasheet). VGluT1 labels excitatory synaptic inputs in all major SOC nuclei of mice (Fischl et al., 2016), bats (Pätz et al., 2022), and in the MSO of gerbil (Callan et al., 2021).…”
Section: Methodsmentioning
confidence: 99%